KEAKTORAN NANIK SETYARINI DALAM PERTUNJUKAN WAYANG ORANG SRIWEDARI SURAKARTA - Widyastuti, Mamik (Institut Seni Indoensia Surakarta, 2009)
This article will strives a field of Nanik Setyarini as an dance-actrees on the wayang orang performance of Sri Wedari, Surakarta. Nanik Setyarini’s acting process has been built since her childhood while she get along by watching wayang performance. Her sensitive abilities to the wayang performance had examined her to start her dancing practice and brought her to join the wayang groups of Sri Wedari, from her role as a supporting dancer to her role as a main dance-actrees as a wayang Srikandi, at least she become a director of wayang performance of Sri Wedari. Nanik’s dedication of her dancer-actrees’s entities to the wayang performance of Sri Wedari at Surakarta seems her role as a wayang Srikandi presently. Nanik Setyarini has her gandar excellence, dance movement expression, dialogues, tembang singing, musical sensibility, and her excellence of acting dedication on a wayang’s she taken role entirely.Keyword : acting dedication, Nanik Setyarini, excellence, wayang orang